Application of green synthesized silver nanoparticles in cancer treatment—a critical review. (3rd September 2021) - Jabeen, Shazina; Qureshi, Rahmatullah; Munazir, Mehmooda; Maqsood, Muhammad; Munir, Mubashrah; Shah, Syed Sabir Hussain; Rahim, Bakht Zareen
Abstract: With the breakthrough in advance technologies, researchers are looking to devise novel approaches to control different types of deadly cancers. Progress in medicinal plants research and nanotechnology has drawn scientist's attention toward green synthesis of metallic nanoparticles by exploiting plants secondary metabolites owing to its advantage over routinely used physical and chemical synthesis (simple, one step approach to reduce and stabilize bulk silver into silver nanoparticles (AgNPs), cost effectiveness, energy efficient, biocompatibility and therapeutic significance). Owing to control size, shape and functional surface corona, AgNPs hold considerable potentiality for therapeutic applications by opting different mechanistic pathways such as mitochondrial disruption, DNA fragmentation, cell membrane disruption, interruption of cellular signaling pathways, altered enzyme activity and reactive oxygen species (ROS) production leading to apoptosis etc In this review, we discussed the green synthesized AgNPs in the possible cancer treatment by harnessing phytochemicals present in plant extract. In addition, this review also provides recent advances and achievements in utilization of green synthesized AgNPs in cancer treatment and proposes mechanistic action for their anticancer and cytotoxic potential. By understanding the mechanistic action of AgNPs responsible for their therapeutic efficacy will help to devise customized therapies and treatment against cancer as a potential cancer therapeutic tool.